1987
DOI: 10.3177/jnsv.33.341
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shiitake(Lentinus edodes) and maitake(Grifola frondosa) mushrooms on blood pressure and plasma lipids of spontaneously hypertensive rats.

Abstract: To study the effect of Shiitake (Lentinus edodes) and Maitake (Grifola frondosa) on hypertension, spontaneously hypertensive rats (SHR) were fed a diet containing 5% mushroom powder and 0.5 NaCl solution as drinking water for 9 weeks. The dietary mushrooms decreased the blood pressure. The plasma free cholesterol level decreased in Shiitake-fed animals, whereas in Maitake-fed animals the total choles terol level decreased. There was no difference in the plasma triglyceride and phospholipid levels among the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
58
0
2

Year Published

1998
1998
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(65 citation statements)
references
References 8 publications
5
58
0
2
Order By: Relevance
“…Their results clearly showed that the cultured broth had an anti-hepatitis B virus activity in vitro and protected mice from liver damage in vivo. On the other hand, different studies reported the relationship between low plasma cholesterol levels and mushrooms consumption [67][68][69][70]. In animal experiments, Kabir et al [71] investigated the dietary effect of G. lucidum on blood pressure and their results showed a significant reduction of the plasma cholesterol level in animals fed with G. lucidum, and these observations have been reported previously.…”
Section: Mechanisms Of Action Of G Lucidum Polysaccharides and Terpensupporting
confidence: 51%
“…Their results clearly showed that the cultured broth had an anti-hepatitis B virus activity in vitro and protected mice from liver damage in vivo. On the other hand, different studies reported the relationship between low plasma cholesterol levels and mushrooms consumption [67][68][69][70]. In animal experiments, Kabir et al [71] investigated the dietary effect of G. lucidum on blood pressure and their results showed a significant reduction of the plasma cholesterol level in animals fed with G. lucidum, and these observations have been reported previously.…”
Section: Mechanisms Of Action Of G Lucidum Polysaccharides and Terpensupporting
confidence: 51%
“…L. edodes inhibits the growth of tumor cells, the replication of herpes simplex virus, HIV infection, and blood cholesterol level (Fujii et al, 1978;Hamuro et al , 1980;Sakar et al, 1993;Suzuki et al , 1989 ;Kabir et al , 1987). C.…”
Section: Abstract: Protoplast Fusion Lentinula Edodes Coriouls Vesimentioning
confidence: 99%
“…Another hypocholesterolemic compound of fungal origin is D-eritadenine, 2(R), 3(R)-dihydroxy-4-(9-adenyl)-butanoic acid (Figure 1), found in the shiitake mushroom, Lentinus edodes [2,3]. The shiitake mushroom has been shown to lower the blood cholesterol in both animals and humans [4][5][6], and the cholesterol reducing mechanism of eritadenine has been investigated in several studies on rats [2,3,[7][8][9][10]. The complete hypocholesterolemic mechanism of eritadenine remains to be clarified, but it has been shown that eritadenine accelerates the removal of blood cholesterol, with no indications of the compound inhibiting the biosynthesis of cholesterol [10], unlike the statins [1].…”
Section: Introductionmentioning
confidence: 99%